2019
DOI: 10.1002/adom.201901092
|View full text |Cite
|
Sign up to set email alerts
|

Giant Electric Bias‐Induced Tunability of Photoluminescence and Photoresistance in Hybrid Perovskite Films on Ferroelectric Substrates

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adom.201901092. Electric Bias-Induced ModulationHybrid perovskites (HPs), particularly methylammonium lead iodide (CH 3 NH 3 PbI 3 , hereafter MAPbI 3 ), have attracted enormous attention owing to their outstanding optoelectronic properties, such as tunable bandgap in the visible range, [1,2] long diffusion length, [3,4] superb optical absorption, [5] small exciton binding energy, [6] high ambipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Metal‐halide perovskites have received intense research efforts owing to their extraordinary optical and electrical properties 18–22. Besides solution‐processed polycrystal films, bulk crystals, and nanocrystals, large‐scale ultrathin perovskites via vapor‐phase growth have attracted intensive research efforts 23–28.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐halide perovskites have received intense research efforts owing to their extraordinary optical and electrical properties 18–22. Besides solution‐processed polycrystal films, bulk crystals, and nanocrystals, large‐scale ultrathin perovskites via vapor‐phase growth have attracted intensive research efforts 23–28.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Also, the lattice change is around 0.01% under an applied electric field for only 0.06 V µm -1 , so does the reported electrostrictive response. [26] It is reported that the strain plays an indispensable role in influencing the electronic band structure of perovskites and the lattice deformation can give rise to the modulation of photoresistance for MAPbI 3 film. [26,29] Thus, we propose that the electrostriction causes the lattice deformation which can affect the photoresponse behavior of perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…To be noted, a V-shaped behavior corresponds to the incoherence of ΔR/R light on bias polarity, as shown in Figure 3B, which also agrees with the strain change of MAPbI 3 film under different bias. Importantly, it further indicates the dominant role of the lattice deformation in the photoresistance modulation, [26] which is subjected to further analysis. Furthermore, the bias-dependent R light of MAPbI 3 film is also measured under different irradiation powers in Fig- ure 3C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations